Age Is (Not) Just a~Word—A Bourdieusian Perspective on the Social Construction of Age, Ageing, and Generations (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2025)
Mass media and sociopolitical and academic discourses on ageing are characterised by a~diffuse and often essentialist use of the concepts of age, ageing, and generation. Based on an interview with Bourdieu on “Youth Is Just a~Word” and philosophical reflections on the semantics of age and ageing, the social-ontological status of age and generation classifications as arbitrary segmentations of a~temporal continuum will therefore first be discussed. However, the life phase of old age was not the focus of Bourdieu's work, so his scattered statements on old age are too undifferentiated and stereotypical for an approach based on the sociology of ageing. In order to gain further building blocks for a~critical gerontology “with Bourdieu and beyond him”, additional sociological and gerontological perspectives on the social construction of age are presented. On this foundation, a~model of the dialectic of symbolic and material constructions of age is presented, which regards “age” as a~symbolic means for the field-specific inclusion and exclusion of individuals, “ageing” as a~lifelong process of opening and closing life chances, and “generations” as socially constructed groups of adjacent age cohorts that compete for access to resources and social positions. The social construction of age, ageing, and generations is conceived of as an institutional, cultural, interactional, and individual process that builds on the material and physical basis of class-specific living conditions and in turn influences and changes them. – – Massenmediale, sozialpolitische und fachwissenschaftliche Diskurse über Altersfragen sind durch einen diffusen und oft essentialistischen Gebrauch von Alters- und Generationenbegriffen geprägt. Ausgehend von einem Interview mit Bourdieu zu ,,Jugend ist nur ein Wort“ und sprachphilosophischen Überlegungen zur Semantik von Alter und Altern wird daher zunächst der sozialontologische Status von Alters- und Generationenklassifikationen als willkürliche Segmentierungen eines zeitlichen Kontinuums diskutiert. Die Lebensphase Alter stand allerdings nicht im Fokus des Werks von Bourdieu, sodass seine verstreuten Aussagen zum höheren Alter für eine alterssoziologische Grundlegung zu undifferenziert und stereotyp sind. Um weitere Bausteine für eine praxeologische Gerontologie ,,mit Bourdieu und über ihn hinaus“ zu gewinnen, werden weitere soziologische und gerontologische Perspektiven auf die soziale Konstruktion von Alter und Altern vorgestellt. Darauf aufbauend wird ein Modell zur Dialektik symbolischer und materieller Alterskonstruktionen vorgestellt, das ,,Alter“ als symbolisches Mittel zur feldspezifischen Inklusion und Exklusion von Menschen, ,,Altern“ als lebenslangen Prozess der Öffnung und Schließung von Lebenschancen und ,,Generationen“ als sozial konstruierte Gruppen benachbarter Alterskohorten versteht, die um den Zugang zu Ressourcen und sozialen Positionen konkurrieren. Die soziale Konstruktion des Alters, des Alterns und der Generationen wird als institutioneller, kultureller, interaktionaler und individueller Prozess begriffen, der auf der materiellkörperlichen Basis klassen- und schichtspezifischer Lebenslagen beruht und diese wiederum beeinflusst und verändert.
Keywords: 300; Age classes; Age classifications; Age boundaries; Critical gerontology; Social constructivism; Social ontology; Altersklassen; Altersklassifikationen; Altersgrenzen; Kritische Gerontologie; Sozialkonstruktivismus; Sozialontologie